Inhibition of Aflatoxin Production of Aspergillus flavus by Lactobacillus casei - Chang, Injeong (The Korean Society of Mycology, 2007)
Lactobacillus casei KC-324 was tested for its ability to inhibit aflatoxin production and mycelial growth of Aspergillus flavus ATCC 15517 in liquid culture. Aflatoxin B(1) biosynthesis and mycelial growth were inhibited in both simultaneous culture and individual antagonism assays,suggesting that the inhibitory activity was due to extracellular metabolites produced in cell-free supernatant fluids of the cultured broth of L. casei KC-324. In cell-free supernatant fluids of all media tested,deMan,Rogosa and Sharpe broth,potato dextrose broth,and Czapek-Dox broth + 1% yeast extract showed higher antiaflatoxigenic activity. In these case, fungal growths, however, was not affected as measured by mycelial dry weight. The antiaflatoxigenic metabolites from L. casei KC-324 were produced over wide range of temperatures between 25℃ and 37℃. However, these metabolites were not thermostable since the inhibitory activity of the supernatant was inactivated within 30 minutes at 100℃ and 121℃. The inhibitory activity was not influenced by changing pH of supernatant between 4 and 10. However,the antiaflatoxigenic activity was slightly reduced at pH 10.